Estimating the Extent of Impervious Surfaces and Turf Grass across Large Regions1. (4th September 2013) - Claggett, Peter R.; Irani, Frederick M.; Thompson, Renee L.
Abstract The ability of researchers to accurately assess the extent of impervious and pervious developed surfaces, e.g., turf grass, using land‐cover data derived from Landsat satellite imagery in the Chesapeake Bay watershed is limited due to the resolution of the data and systematic discrepancies between developed land‐cover classes, surface mines, forests, and farmlands. Estimates of impervious surface and turf grass area in the Mid‐Atlantic, United States that were based on 2006 Landsat‐derived land‐cover data were substantially lower than estimates based on more authoritative and independent sources. New estimates of impervious surfaces and turf grass area derived using land‐cover data combined with ancillary information on roads, housing units, surface mines, and sampled estimates of road width and residential impervious area were up to 57 and 45% higher than estimates based strictly on land‐cover data. These new estimates closely approximate estimates derived from authoritative and independent sources in developed counties.